Genome-Wide Identification of Papain-Like Cysteine Proteases in Gossypium hirsutum and Functional Characterization in Response to Verticillium dahliae - Zhang, Shuqin; Xu, Zhongping; Sun, Heng; Sun, Longqing; Shaban, Muhammad; Yang, Xiyan; Zhu, Longfu (Frontiers in Plant Science, 2019)
Cotton, a natural fiber producing crop of huge importance, is often prone to attack of Verticillium dahliae. Papain-like cysteine proteases (PLCPs) constitute a large family in plants and were proposed to involve in plant defense against pathogen attack in a number of studies. However, there is no detailed characterization of PLCP genes in cotton against infection of V. dahliae. In this study, we carried out a genome-wide analysis in cotton and identified seventy-eight PLCPs, which were divided into nine subfamilies based on their evolution phylogeny: RD21 (responsive to desiccation 21), CEP (cysteine endopeptidase), XCP (xylem cysteine peptidase), XBCP3 (xylem bark cysteine peptidase 3), THI, SAG12 (senescence-associated gene 12), RD19 (responsive to desiccation 19), ALP (aleurain-like protease) and CTB (cathepsin B-like). Genes in each subfamily exhibit a similar structure and motif composition. The expression patterns of these genes in different organs were examined, and subfamily RD21 was the most abundant in these families. Expression profiles under abiotic stress showed that thirty-five PLCP genes were induced by multiple stresses. Further transcriptome analysis showed that sixteen PLCP genes were up-regulated in response to V. dahliae in cotton. Among those, GhRD21-7 showed a higher transcription level than most other PLCP genes. Additionally, over-expression of GhRD21-7 led to enhanced resistance and RNAi lines were more susceptible to V. dahliae in cotton. Our results provide valuable information for future functional genomic studies of PLCP gene family in cotton.